ANALISIS YURIDIS PEMAKNAAN PASAL 33 (1) UUD 1945 BERDASARKAN PANCASILA DARI PERSPEKTIF HUKUM TATA NEGARA - Jawalsen Ralian; Aartje Tehupeiory; Fernando Silalahi (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
The purpose of this research is to 1) Describe and analyse how the meaning of Article 33 paragraph (1) of the 1945 Constitution based on Pancasila and the perspective of constitutional law, and 2) Describe and analyse how legal certainty is in favour of realising social welfare and justice in social life in the Pancasila nation. The writer conducts this research using John Rawls' theory of Justice and the conceptual theory of Pancasila. The research method used in this study uses qualitative research methods where the research approach is juridical normative. The data collection techniques carried out by the writer are triagulation (combined) data collection techniques, inductive / qualitative data analysis, and qualitative research results, and qualitative research results are more emphasis on the meaning than generalisation. The results of the research that the author gets are the meaning of Article 33 (1) of the 1945 Constitution based on Pancasila from the perspective of Constitutional Law, that is, non-profit economic enterprise is the idea of the founding fathers of the nation which even before Indonesia's independence had prepared a social welfare state.